The plate economy: capitalism, food and nutrition in the service society - Alan Gutiérrez Vilchis; Miguel Ángel Karam Calderón (Social Medicine Publication Group, 2024)
This essay explores the relationship between food, nutrition, and Marxist theory in a capitalist society. Through an in-depth analysis of socio-economic structures and power relations, it examines how food production, distribution and consumption are influenced by these forces. Reference is made to key works by Marx, such as "Capital" and "The Communist Manifesto," to illustrate how labor exploitation and economic inequality are reflected in nutrition and access to food. In addition, it discusses how the service/information society interacts with food and nutrition in the context of Marx's historical materialism. This essay provides a critical and enlightening perspective on an important topic relevant to our daily lives.